Rozważania wokół strategii finansowania wewnętrznego przedsiębiorstwa - Grabowska, Marlena (The Considerations of the Internal Financing Strategy of the Enterprise, 2005)
In the article the attempt of characterizing the internal financial sources of the enterprise has been taken. It also has been analyzed the issues and role of internal financial sources in the current and developmental activity of the enterprise.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1060, s. 142-151